The application and prospects of dental implant robot technology in clinical teaching of oral implant specialty - ZHOU Weikai, MAN Yi, JIANG Yuhuan, WANG Jing (Kouqiang yixue)
Objective To utilize the dental implant robot in the clinical instruction of oral implantology in order to popularize the technology and serve the medical education. Methods The effectiveness of the robotics teaching approach was assessed through a questionnaire. Results The dental implant robot technology has certain advantages in the clinical teaching of oral implant majors. Conclusion With the increasing popularity of digital implantation, the emerging dental implant robot has a wide range of applications and many advantages. It is very necessary to introduce it into the clinical teaching of oral implant majors.